Extra-Virgin Olive Oil Extracted Using Pulsed Electric Field Technology: Cultivar Impact on Oil Yield and Quality - Veneziani, Gianluca; Esposto, Sonia; Taticchi, Agnese; Selvaggini, Roberto; Sordini, Beatrice; Lorefice, Antonietta; Daidone, Luigi; Pagano, Mauro; Tomasone, Roberto; Servili, Maurizio (Frontiers in Nutrition, 2019)
The main operators of the olive oil sector are continuously involved in the development of the olive oil mechanical extraction process with the common aim of increasing both the quality and the oil extraction yield coupled with the potential enhancement of the working efficiency of the olive mill. The pulsed electric field is a recently studied technological innovation for the improvement of olive oil extraction technology. The impact of the pulsed electric field on the diffusion of oil and microconstituents, determined by the disruption effects on olive cell tissues carried out by the nonthermal method, was evaluated. A pulsed electric field can increase the permeability and breaking of the cell membranes with a consequent positive result on oil extractability and quality, mainly related to the compounds involved in the health and sensory properties of extra virgin olive oil. The pulsed electric field was tested on three Italian olive cultivars (Carolea, Coratina and Ottobratica). The results showed a positive impact of the new technology on the oil yield, with an increase ranging from 2.3% to 6%, and on the concentration of hydrophilic phenols, with an increase ranging from 3.2% to 14.3%, with respect to the control tests. The data of the main compounds related to the health and sensory notes also showed high variability as a consequence of the genetic origins of the olive cultivars.